ANALYSIS OF THE EFFECT OF CONVERSION OF RICE FIELDS ON AGRICULTURAL PRODUCTIVITY IN EAST NUSA TENGGARA - Faisal Adi Saputra; Lorentino Togar Laut; Putra Arif Budiman (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2021)
The centrality of agriculture as one of the large sectors that sustain Indonesia's GDP does not make this sector free from various problems. The transfer of the function or conversion of agricultural land to nonfarm is a serious problem that occurs in Indonesia, especially in East Nusa Tenggara. The explosion of population growth and the shift of the economy to the manufacturing sector are the strongest reasons for the narrowing of agricultural land. The productivity of agricultural products is something that needs to be considered. This study uses descriptive analysis techniques and supported data from BPS. The results of this study showed no relationship between the phenomenon of transfer of agricultural land functions and agricultural productivity in East Nusa Tenggara.